Novel Potential Biomarker of Adult Cardiac Surgery-Associated Acute Kidney Injury - Chen, Zujun; Hu, Zhenliang; Hu, Yiqing; Sheng, Yixuan; Li, Yuan; Song, Jiangping (Frontiers in Physiology, 2020)
Background Acute kidney injury (AKI) occurs in about 30% of patients with cardiac surgery, but the pathogenesis of cardiac surgery-associated acute kidney injury (CSA-AKI) remains unclear and there are no predictive biomarkers or diagnostic criteria specific for CSA-AKI beyond the general clinical variables for AKI like serum creatinine (SCr). Methods and Results We measured the plasma levels of 48 cytokines within 24 h after cardiac surgery in a total of 306 adult patients including 204 with and 102 without AKI, and then evaluated the diagnostic efficacy of these cytokines for the development of CSA-AKI via ANOVA and Pearson correlation analysis. Among these 48 cytokines, 20 of them were significantly different in the AKI patients compared with the non-AKI patients. In particularly, 13 cytokines displayed tremendous changes with the P < 1E–5. Moreover, 10 of the 48 cytokines in the plasma were significantly different among the patients with different stages of AKI. Specifically, 6 cytokines exhibited immense differences with the P < 1E–5. Additionally, 7 of the 48 cytokines have the correlation coefficient of r > 0.5 with the postoperative changes of SCr after cardiac surgery. Conclusion Taken all the results together, IFN-γ and SCGF-β were the most relevant two cytokines that were not only remarkably changed in adult CSA-AKI patients during the first 24 h after cardiac surgery, but also significantly correlated with the postoperative changes of SCr after cardiac surgery. Therefore, IFN-γ and SCGF-β might be novel predictive plasma biomarker, as well as potential therapeutic targets specific for adult CSA-AKI.